2019
DOI: 10.3389/fmicb.2019.02233
|View full text |Cite
|
Sign up to set email alerts
|

An iPSC-Derived Myeloid Lineage Model of Herpes Virus Latency and Reactivation

Abstract: Herpesviruses undergo life-long latent infection which can be life-threatening in the immunocompromised. Models of latency and reactivation of human cytomegalovirus (HCMV) include primary myeloid cells, cells known to be important for HCMV latent carriage and reactivation in vivo. However, primary cells are limited in availability, and difficult to culture and to genetically modify; all of which have hampered our ability to fully understand virus/host interactions of this persistent human pathogen. We have now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Previous studies have shown efficacy of I-BETs in various models of human myeloid leukemia, and many inhibitors are now in clinical development (phases I, II, and III) as single treatments of both oncology and nononcology diseases ( 66 ). Our work also shows that I-BETs can initiate IE gene expression from HCMV latently infected CD34+ cells, which are good models for HCMV latent infection ( 69 ), whereas HDACis such as CHR-4487 (a myeloid-selective HDACi) can have differential effects on CD34+ models with little response in Kasumi-3 cells, consistent with others’ previous work ( 70 ). Hence, with good compound penetrance and known immune surveillance in bone marrow, treatment with I-BETs like GSK726 may also allow targeting of latently infected bone-marrow resident pluripotent CD34+ progenitor cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown efficacy of I-BETs in various models of human myeloid leukemia, and many inhibitors are now in clinical development (phases I, II, and III) as single treatments of both oncology and nononcology diseases ( 66 ). Our work also shows that I-BETs can initiate IE gene expression from HCMV latently infected CD34+ cells, which are good models for HCMV latent infection ( 69 ), whereas HDACis such as CHR-4487 (a myeloid-selective HDACi) can have differential effects on CD34+ models with little response in Kasumi-3 cells, consistent with others’ previous work ( 70 ). Hence, with good compound penetrance and known immune surveillance in bone marrow, treatment with I-BETs like GSK726 may also allow targeting of latently infected bone-marrow resident pluripotent CD34+ progenitor cells.…”
Section: Discussionsupporting
confidence: 91%
“…TB40/E mCherry -US28-3XFLAG and TB40/E mCherry -US28Δ have been described previously (19). TB40/E gfp (82) and TB40/E BAC4 SV40 mCherry IE2-2A-GFP (83) were kind gifts from E. A. Murphy, SUNY Upstate Medical University. TB40/E BAC4 IE2-eYFP has been described previously (60, 84).…”
Section: Methodsmentioning
confidence: 99%
“…TB40/E mCherry -US28-3XFLAG and TB40/E mCherry -US28Δ have been described previously 19 . TB40/E gfp 47 and TB40/E BAC4 SV40 mCherry IE2-2A-GFP 48 were kind gifts from E.A. Murphy, SUNY Upstate Medical University.…”
Section: Methodsmentioning
confidence: 99%